Population analysis of African Y-STR profiles with UniQ TYPER™ Y-10 genotyping system. (December 2017) - D'Amato, Maria Eugenia; Kasu, Mohaimin
Abstract: The Y-STR prototype UniQ Typer™ Y-10 was tested in 957 males from 8 South African ethnic groups. The overall DC = 0.909, and DC = 1 in three groups implies an important capacity to resolve the male component(s) of sexual assault evidence. This prototype offers an invaluable feature in a country with the highest rape incidents in the world. In addition, the kit shows potential for genealogical and population studies.